Perlindungan Hukum Hak Kekayaan Intelektual Terhadap Hak Cipta Berdasarkan Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta - Antan Yuniar (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
Copyright is an exclusive right for creators or recipients of rights to announce or reproduce their creations or give permission for them without reducing restrictions according to applicable laws and regulations. Issues regarding intellectual property rights, one of which is copyright, in today's free trade are things that must be considered. Therefore, it is important to protect copyright for creators so that their ideas, creativity and works are not plagiarized by others. In this case, the legal protection for copyright that can be given is based on Law Number 28 of 2014 concerning Copyright. The method used in this study is normative with a qualitative approach and the sources used are Law Number 18 of 2014, books, journals and articles related to the problems studied.